Use of Condensate Combined with Hydrocking Palm Oil Products for Improving The Quality of Premium - Muhammad Said (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
A research about hydrocracking of Crude Palm Oil (CPO) has been conducted using the catalyst Cr/active natural zeolite. Hydrocracking of CPO was conducted at the temperature variations of 300 oC, 400 oC, 500 oC and 600 oC to determine the optimum temperature based on the density and viscosity of the product of hydrocracking. Hydrocracking of CPO was also varied with the weight of catalysts 0.5 g, 1 g, 1.5 g, 2 g and 2.5 g using an optimum temperature. Products of hydrocraking were vacuum distilled and calculated for the percentage of area products and gasoline fractions. The results showed the optimum temperature at 400 oC the optimum weight of catalyst was 2.5 g with percentage of product was 1.2779 % and the area fraction of gasoline 469.953. Nature additives obtained from hydrocracking products at the optimum conditions blended with premium and condensate to see how it influences on octane number change. Nature additives added to premium increase the octane number from 87.4 to 87.8, while the addition of condensate lower the octane number.